HUBUNGAN ANTARA KEKERASAN DALAM RUMAH TANGGA DENGAN POSTPARTUM BLUES PADA WANITA POSTPARTUM DI HUNIAN TETAP KECAMATAN CANGKRINGAN DAERAH PASCA BENCANA ERUPSI MERAPI - , LEA DISTI ARIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Eruption of Mount Merapi that occurred in 2010 is an event that is traumatic and lead to impact on the mental health of the affected population. The woman is one of the populations that are vulnerable to disasters. Problems that arise in women caused by the disaster is domestic violence. Women who are exposed to violence will be disturbed in the process of adaptation because of the physical and psychological changes during the postpartum period and the process of adjustment to a new role as a mother. It will cause emotional stress in some women because they feel depressed postpartum. Stress is not treated immediately will continue into the postpartum blues Aim: This study aims to know the association between domestic violence and postpartum blues among postpartum women in permanent shelter in cangkringan area after the eruption of Mt. Merapi. Method: This research uses a non-experimental study with a quantitative approach. The study design was cross-sectional. Research sample were 35 postpartum women who live in permanent shelter Cangkringan area after Merapi eruption and gave birth at the maternity clinic Azizah. Instrument used was the Edinburgh Postnatal Depression Scale (EPDS) and a questionnaire referring to the questionnaire SEHATI 2000. Analysis of the data using the chi-square statistical test. Result: There is a association between psychological violence (p = 0.003), physical violence (p = 0.017), sexual violence (p = 0.001) and economic violence (p = 0.027) with postpartum blues. Conclusion: Domestic violence in the form of psychological, physical, sexual and neglect of economic (economic violence) had a significant association with postpartum blues.